Providing a Causal Model of Digital Leadership Factors in the Formation of an Innovative Organizational Culture in Universities of Mazandaran Province - Maleki, Rojan; Niazazari, Marzieh; Taghvaee Yazdi, Maryam (Assessment and Practice in Educational Sciences, 2026)
The purpose of the present study was to provide a causal model of digital leadership factors in the formation of an innovative organizational culture in the universities of Mazandaran Province. The research method was applied in terms of purpose and descriptive–survey in nature. The statistical population included all employees of Islamic Azad University branches in the cities of Sari, Babol, Tonekabon, Chalous, Neka, and Behshahr in Mazandaran Province (1,030 individuals). The sampling method was proportional cluster random sampling based on university units, and the sample size was determined to be 280 individuals using Cochran’s formula. A researcher-made questionnaire was used to collect data for the two variables of digital leadership and innovative organizational culture. The face, content, and construct validity of the instrument were examined and confirmed by academic supervisors, advisors, and subject-matter experts. In descriptive statistics, the mean, standard deviation, frequency distribution tables, and charts were presented for each variable, and this process was performed using SPSS software. In inferential statistics, the Kolmogorov–Smirnov test was used to examine the normality of data distribution, and to address the research questions, single-sample and independent t-tests, correlation coefficients, exploratory factor analysis, and structural equation modeling (including exploratory and confirmatory factor analysis) were employed. In the inferential section, the research hypotheses were tested using SPSS as well as AMOS. The results obtained from AMOS software were interpreted using the structural equation modeling approach. Path analysis results indicated that digital leadership has a positive, direct, and significant effect on innovative organizational culture.